Gamification in Islamic Religious Education Effectiveness and Challenges in Increasing Students' Learning Motivation - Desy Safitri; Dwi Noviani; Lisa Anggraini; Dian Vitasari (Journal Analytica Islamica, 2024)
Gamification, an approach that integrates game elements into non-game contexts, has attracted attention as an innovative tool for increasing students' learning motivation. In the context of Islamic education, the application of gamification offers great potential to make religious learning more interesting and interactive. This research aims to explore the effectiveness of gamification in increasing students' learning motivation in Islamic religious subjects, as well as identifying challenges that may be faced in its implementation. Literature studies show that gamification can create a more enjoyable learning environment, increase student engagement, and encourage the development of critical thinking skills. Elements such as points, badges, levels, and competitions can motivate students to achieve learning goals. However, there are several challenges in implementing gamification in Islamic education. One of them is the need to adapt game elements to Islamic values. In addition, limited resources and technological infrastructure can be an obstacle.